PEMBELAJARAN PJOK BERBASIS AKTIVITAS FISIK UNTUK MENGHADAPI TANTANGAN KESEHATAN PESERTA DIDIK MASA KINI - M. Abdul Majid Abdalah; Dede Indra Maryadi; Abdul Rohman; Asep Sahrul Gunawan (STKIP Subang, 2026)
Physical Education, Sports, and Health (PJOK) learning has a strategic role in addressing contemporary student health challenges, such as low levels of physical activity, sedentary behavior, and declining physical fitness. This study aims to examine the role and effectiveness of physical activity-based PJOK learning in improving students’ health conditions through a literature review approach. The research employed a descriptive-analytical literature study by reviewing scientific articles, books, and reports from reputable national and international sources published within the last ten years. Data were collected through systematic searches in academic databases and analyzed by categorizing, synthesizing, and interpreting relevant findings related to physical activity, physical education learning, and student health outcomes. The results of the literature review indicate that physical activity-based PJOK learning contributes positively to improving physical fitness, reducing sedentary behavior, and fostering healthy lifestyle habits among students. Furthermore, PJOK learning that emphasizes active participation supports not only physical development but also students’ awareness and attitudes toward long-term health maintenance. These findings suggest that strengthening physical activity-based PJOK learning is essential as a strategic educational approach to respond to current student health challenges.